Efficiency of national innovation systems: Poland and Bulgaria in the context of the Global Innovation Index - Barbara Jankowska; Anna Matysek-Jędrych; Katarzyna Mroczek-Dąbrowska (Comparative Economic Research. Central and Eastern Europe, 2017)
The purpose of this paper is to explain how national innovation systems may transform innovation input into innovation output in different counties. Using the Global Innovation Index (GII) we discuss what can be understood by the term "innovation" and how it is translated into the national level. The research question is founded on the assumption that the higher the innovation input, the higher the innovation output attained by a country. We use cluster analysis to verify our assumption, referring to a total of 228 countries. Afterwards we conduct a more in-depth analysis of two cases (Poland and Bulgaria), where the research question does not find confirmation. Using the cross-comparison method we aim to verify how and why national innovation systems failed (or succeeded) in creating innovations.
Keywords: O33; O38; 330; national innovation system; Poland; Bulgaria; Global Innovation Index